A Bibliometric-Systematic Review of Digital Transformation in Indonesia’s Economic Development - Susanto, Arva Athallah; Lu, Ji; Aryadimas Suprayitno; Hadi, Nizar Hosfaikoni (Journal of Advances in Information and Industrial Technology, 2026)
Digital transformation has become a key driver of technological innovation, economic restructuring, and institutional change in Indonesia, yet systematic synthesis of its scholarly development remains limited. This study addresses this gap by applying an integrated bibliometric and systematic literature review (SLR) approach to examine the intellectual structure, thematic evolution, and research dynamics of digital transformation scholarship in Indonesia from 2017 to 2025. Using Scopus-indexed publications, centrality-based bibliometric analysis identifies eleven major research clusters shaping the field. Among these, digital transformation emerges as the most structurally influential cluster, exhibiting the highest betweenness, closeness, and PageRank centrality, and functioning as an intellectual hub linking MSMEs, sustainability, circular economy, smart cities, environmental economics, and organizational transformation. Intermediate clusters, including digital economy, economics, MSMEs, and circular economy, reinforce the core discourse, reflecting growing academic attention to Industry 4.0, artificial intelligence, cybersecurity, and sustainable development. Smaller clusters, such as fintech, digitization, and developing countries, represent emerging research trajectories focused on governance, resilience, and digital inclusion. The SLR component complements the bibliometric mapping by synthesizing theoretical contributions, methodological trends, and research gaps within key thematic clusters, thereby enhancing conceptual coherence. The novelty of this study lies in its integrative mixed-method design, offering the most comprehensive mapping of Indonesia’s digital transformation literature to date. The findings provide strategic directions for future interdisciplinary research and generate policy-relevant insights to support inclusive and sustainable digital transformation aligned with national and global development agendas.